Implementation of Community Service in The Introduction of History in the Sembulungan Peninsula, Banyuwangi Regency, East Java Province Indonesia - Agus Mursidi; Tofan Priananda Adinata; Abdul Shomad; Dhalia Soetopo; Miskawi; Atim Hariadi (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2021)
One of the relics whose existence must be preserved and preserved is in Banyuwangi Regency, precisely in Alas Purwo National Park (TN Alas Purwo), a national park located in Banyuwangi covering an area of 43,420 hectares. In addition to having a diversity of flora and fauna in the Alas Purwo National Park area, there are also many objects and buildings of the past, especially on the Sembulungan peninsula, which was formerly known as an entry and exit route for colonial trade commodities. However, let alone the student community who are academics who are not very familiar with the relics on the Sembulungan peninsula, the method used in this service is qualitative analysis by coming to the location directly and conducting observations and collecting data through structured interviews with a triangulation approach. The results show that students' insight has increased by looking at the relics of the Japanese military in maintaining power in the form of bunkers, cannons, and military strategies developed on the Sembulungan peninsula for maritime security.